Evaluasi Pengendalian Sistem Informasi Pengiriman pada TL - Nelly, Nelly; Susiana, Liu; Kialiawati, Wenni; Meiry, Meiry; Gui, Anderes (Bina Nusantara University, 2011)
The purpose of this study is to evaluate the control systems on the TL shipping information, in order to discern weaknesses or problems in delivery of enterprise information systems control using CobIT approach. The research method used is the data collecting by observation, checklists, interviews, and literature study. The results achieved are findings and issue recommendations that provide an illustration about a control of the running information delivery systems. From the illustration it is known that on the company?s control of information delivery system, there are still many things that have not been up to standard. The conclusion obtained is that the control of information delivery systems that have been implemented meets only partially the standards set small, so it still needs much improvement.